2004
DOI: 10.4049/jimmunol.172.8.5086
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Selection Defects Underlie the Development of Diabetogenic APCs in Nonobese Diabetic Mice

Abstract: One mechanism whereby B cells contribute to type 1 diabetes in nonobese diabetic (NOD) mice is as a subset of APCs that preferentially presents MHC class II-bound pancreatic β cell Ags to autoreactive CD4 T cells. This results from their ability to use cell surface Ig to specifically capture β cell Ags. Hence, we postulated a diabetogenic role for defects in the tolerance mechanisms normally blocking the maturation and/or activation of B cells expressing autoreactive Ig receptors. We compared B cell tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
85
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 49 publications
7
85
0
Order By: Relevance
“…5). This difference supported the previous study from our laboratories in which we had shown that in vitro stimulation of purified HEL-specific B lymphocytes derived from IgHEL Â sHEL Dbl-Tg donors with anti-IgM and anti-CD40 Ab (mimicking Ag and T-cell encounter), resulted in reversal of anergy in those cells when derived from donors with the NOD, but not the B6 background [8]. These in vitro experiments also suggested that anergic B lymphocytes on the NOD background were intrinsically more susceptible to a breakdown in self-tolerance upon provision of T-cell help than anergic B lymphocytes from B6 mice.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…5). This difference supported the previous study from our laboratories in which we had shown that in vitro stimulation of purified HEL-specific B lymphocytes derived from IgHEL Â sHEL Dbl-Tg donors with anti-IgM and anti-CD40 Ab (mimicking Ag and T-cell encounter), resulted in reversal of anergy in those cells when derived from donors with the NOD, but not the B6 background [8]. These in vitro experiments also suggested that anergic B lymphocytes on the NOD background were intrinsically more susceptible to a breakdown in self-tolerance upon provision of T-cell help than anergic B lymphocytes from B6 mice.…”
supporting
confidence: 90%
“…According to our previous studies in which IgHEL-Tg B lymphocytes were placed in an environment where HEL was expressed as a ubiquitous neo-self-Ag, the loss of self-tolerance in the B-lymphocyte repertoire of NOD mice occurred in peripheral lymphoid tissues, whereas central tolerance in the BM, manifest by deletion and receptor editing, remained intact [8]. Nevertheless, these studies did not tell us how autoimmune B-lymphocyte responses to b-cell-specific Ag per se occur.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations